2018
DOI: 10.1139/cjfas-2017-0168
|View full text |Cite
|
Sign up to set email alerts
|

Population and individual identification of Chinook salmon in British Columbia through parentage-based tagging and genetic stock identification with single nucleotide polymorphisms

Abstract: A study was undertaken to evaluate whether a parentage-based tagging (PBT) and genetic stock identification (GSI) program has the potential to emulate the results from an existing coded-wire tag (CWT) assessment program in British Columbia. A PBT–GSI approach was used to identify Chinook salmon (Oncorhynchus tshawytscha) to specific populations and brood years where 36 241 individuals from 45 populations were genotyped at 321 single nucleotide polymorphisms (SNPs). Known-origin and known-age age 1 juveniles fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 34 publications
2
73
0
Order By: Relevance
“…Studies consistently show that accurate parentage analysis can be conducted with <100 SNPs (Hayes et al 2005;Anderson and Garza 2006;Hauser et al 2011;Steele et al 2013), even when thousands of potential parents across multiple populations are considered. The concurrent use of markers for PBT and Genetic Stock Identification applications can achieve complete and accurate stock-specific information for both hatchery-and natural-origin fish (e.g., Hess et al 2016aHess et al , 2016bHess et al , 2016cBeacham et al 2017Beacham et al , 2018. As implementation of PBT expanded from the Snake River to the Columbia River basin, more SNPs were incorporated to represent variation in the entire range of these hatchery populations.…”
Section: Development Of Pbt-tools and Techniques Molecular Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies consistently show that accurate parentage analysis can be conducted with <100 SNPs (Hayes et al 2005;Anderson and Garza 2006;Hauser et al 2011;Steele et al 2013), even when thousands of potential parents across multiple populations are considered. The concurrent use of markers for PBT and Genetic Stock Identification applications can achieve complete and accurate stock-specific information for both hatchery-and natural-origin fish (e.g., Hess et al 2016aHess et al , 2016bHess et al , 2016cBeacham et al 2017Beacham et al , 2018. As implementation of PBT expanded from the Snake River to the Columbia River basin, more SNPs were incorporated to represent variation in the entire range of these hatchery populations.…”
Section: Development Of Pbt-tools and Techniques Molecular Markersmentioning
confidence: 99%
“…PBT has also been implemented at some California hatcheries where it was used to examine life history and trait heritabilities of steelhead (Abadía-Cardoso et al 2013). In British Columbia, Canada, several proof-of-concept studies were completed to pave the way for using PBT in sampling Coho (Beacham et al 2017) and Chinook (Beacham et al 2018) Salmon in ocean fisheries. Implementation of PBT is also becoming an international endeavor.…”
Section: Applications-pbt In Fisheries Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice of using GSI for fisheries management purposes began in the 1980s (Pella & Milner, 1987) when genotypes at multiple loci (allozymes) were becoming commonly available. More recently an increasing number of studies analyzing stock mixtures in fisheries have been published (Beacham et al, 2018;Bradbury et al, 2016;Gilbey et al, 2017;Östergren, Nilsson, Lundqvist, Dannewitz, & Palm, 2016;Vaha, Erkinaro, Falkegard, Orell, & Niemela, 2017;Whitlock et al, 2018).…”
Section: Quinnmentioning
confidence: 99%
“…Assignment of progeny to parents through standard exclusion or probability-based methods provides the age as well as the hatchery and family of origin for progeny sampled at any location or time throughout their lives. PBT techniques developed and validated for a number of Pacific salmonids are increasingly being used to provide comprehensive identification and assessment objectives (Beacham et al, , 2018Hess et al, 2016;Steele et al, 2019). Beacham et al (2019) demonstrated the utility of PBT for the aging and identification of southern BC hatchery coho salmon in highly mixed-stock fisheries throughout BC and in adult returns to rivers known as escapements (portion of a salmon population that does not get caught in fisheries and returns to its natal river to spawn).…”
Section: Introductionmentioning
confidence: 99%